Determination of the potency of a cell-based seasonal quadrivalent influenza vaccine using a purified primary liquid standard. (November 2020) - Takahashi, Hitoshi; Fujimoto, Takao; Horikoshi, Fumiaki; Uotani, Tae; Okutani, Mie; Shimasaki, Noriko; Hamamoto, Itsuki; Odagiri, Takato; Nobusawa, Eri
Abstract: In Japan, the practical application of completely cell-based seasonal influenza vaccines is under consideration. Considering the good correlation between the immunogenicity of egg-based influenza vaccines and the hemagglutinin (HA) content determined by the single radial immunodiffusion (SRD) assay, we determined the potency of the first cell-based quadrivalent vaccine experimentally generated in Japan using the SRD assay in this study. A primary liquid standard (PLS) and reference antigen were generated from the purified vaccine virus, and a sheep antiserum was produced against the HA of the vaccine virus. Since the purity of the PLS affects the reliability of vaccine potency testing, the purification steps are significant. We successfully prepared a purified PLS nearly free of cell debris. The HA content in the PLS was first estimated from the total amount of viral protein and the percentage of HA content determined by SDS-PAGE analysis. The HA content in the reference antigen was calibrated to that in the PLS via the SRD assay. The vaccine potency, that is, the HA content in each vaccine, was finally measured using the corresponding reference antigen. Ultimately, the measured vaccine potency of the monovalent vaccine was similar to that of the quadrivalent vaccine.